Identifying Reading Difficulties and Strategies Among EFL Learners in Intensive Reading - Oktari, Nimas Laras; Ariani, Musli; Fitriyah, Siti Masrifatul (EFL Education Journal, 2024)
Intensive reading helps students to understand the meaning of a word and is one of the college courses that is useful in learning. In this study, the researcher identified the difficulties and strategies used by EFL learners in intensive reading. The objective of this research was to identify the difficulties and the strategies used by EFL learners in intensive reading. The research used a qualitative case study that attempted to identifying reading difficulties and strategies among EFL learners in intensive reading. The researcher analyzed the data using thematic analysis model adopted from Braun and Clarke (2006). The result of this research showed that the students’ difficulties were divided into two types: reading difficulties related to learning goals and psychological barriers. When difficulties arise in the areas of learning objectives that students can use to guide their performance with these objectives, it can hinder students' reading comprehension. Studies also found that students face reading difficulties related to psychological barriers such as attention deficits, poor retention, lack of self-confidence, lack of motivation and shyness. The result of this research is expected to be able to give meaningful contributions for, teachers or lecturers, EFL learners and other researchers.